Azbabun Nuzul Ayat Study of Closing the Aurat/Veil/Hijab (Study of Surah Al-Ahzab Verse 59) - M. Nur Gema Ramadhan; Nurlina Sari Ihsanniati; Khoirul Umami (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This article aims to provide an overview to all interested parties regarding how mufassir understand and interpret the verses of the Koran regarding the hijab or covering of the private parts for women. Apart from that, this article also displays the views of the mufassir in understanding this problem. The verses of the Qur'an were revealed to be practiced with all their fadhilah and goodness, including the obligation to cover their private parts for women, which is intended to provide security and comfort for them and the people around them. All the responsibilities that Allah gives to His servants are for the benefit of humans. Therefore, it is hoped that this article will provide a more comprehensive understanding of the obligations of the hijab for women, thereby encouraging a moderate attitude in understanding and practicing it, without blaming other opinions or feeling self-righteous. By expressing the mufassir's understanding of the hijab for women, women are expected to be able to choose the right option according to their needs in the Sharia corridor. In addition, this paper aims to increase public understanding of the hijab issue and reduce unnecessary debate.